Valores de refer??ncia para os testes de caminhada de dois minutos e teste levanta senta em crian??as e adolescentes saud??veis - Silva, Maril??ia Ara??jo da (2018)
Introduction: The two-minute (2MWT) and six-minute walk test (6MWT) and the 5-repetition sit-to-stand test (5-STSt) are often used in children and adolescents to assess functional capacity in health and in their injuries. However, the scarcity (6MWT) or absence (2MWT and STS) of prediction equations for these tests in children and adolescents limits their adequate interpretation. Aims: To establish reference equations for prediction of walking distance for 2MWT, 6MWT, and time spent on 5-STSt test in healthy children and adolescents. Methods: This is a multicenter study with 627 children and adolescents (312 girls) between the ages of 6 and 17 years. Individuals underwent spirometry, leg length (LL) and thigh circumference (TC), 2MWT, 6MWT, and 5-STSt. The independent variables were age, weight, height, body mass index, sex (0: girls, 1: boys), heart rate delta (??HR, peak - rest), participant center (Dummy 1 = SP, 3 = RS and 4 = Natal). Results: The regression analysis determined the following prediction equation for the distance (D) at the 2MWT in children: DW-2MWT (6 to 12 years) = 41.848 ??? (0.818 x weight, Kg) + (130. 695 x height, m) + (0.322 x ???FC) ??? (7.195 x Dummy 1) ??? (15.104 x Dummy 3) (R2 = 0.347; p = 0.009); for teenagers: DW-2MWT (13 to 17 years) = 142.510 + (13. 274 x Sex) + (0.263 x ???FC) + (0.588 x CP, cm) + (12.403 x Dummy 2) (R2 = 0.251; p = 0.002). For the 6MWT, the forecast equation is: DW-6MWT (6 to 12 years) = 123.817 + (5.299 x age, years) + (14.232 x Sex) ??? (3.033 x weight, Kg) + (345 x height, m) + (0.952 x ???FC) ??? (19.052 x Dummy 1) ??? (32.564 x Dummy 3) (R2 = 0.389; p = 0.036); for adolescents, the forecast equation is: DW-6MWT (13 a 17 years) = 224.041 + (24.350 x Sex, being 0 for girls and 1 for boys) + (111.340 x height, m) + (1.252 x ???FC) + (1.511 x LL, cm) + (32.615 x Dummy 2) (R2 = 0.369; p = 0.007). The prediction equation for the time spent (T) to perform the 5-STS is: T-5-STSt (06 a 12 years) = 6.638 + (0.030 x TC) + (1.256 x Dummy 1) ??? (0.508 x Dummy 2) + (0.534 x Dummy 3) (R2 = 0.256; p = 0.04); for teenagers: TSTS -5rep (13 a 17 years) = 8.308 + (0.680 x Dummy 1) ??? (0.631 x Dummy 2) (R2 = 0.203; p = 0.01). The tests were reproducible in the four centers surveyed with intraclass correlation coefficient ranging from 0.85-0.96 for the 2MWT scan; 0.88-0.99 for 6MWT and 0.79 to 0.85 for T-5-STSt. In children, performance was similar in the 2MWT between boys (204.8 ?? 26.5 m) and girls (198.1 ?? 24.6 m). For teenagers the mean DW-2MWT was 222.2 ?? 26.0 (boys) and 209.0 ?? 20.0 (girls). In the 6MWT, the boys walked more than the girls in the age group of 6 to 12 years (594.3 ?? 70.8 m and 576.3 ?? 65.9 m, respectively) and in the 13 to 17 years age group (640.8 ?? 74.7 m and 608.9 ?? 52 m, respectively). Boys and girls obtained similar performance in T-5-STSt (children: 8.1 ?? 1.5 and 8.4 ?? 1.6 s, adolescents 8.5 ?? 1.3 and 8.5 ?? 1.4 s, respectively). Conclusion: The present study established reference equations for Brazilian children and adolescents of walking tests (2MWT and 6MWT) and for 5-STSt. These equations can be used as reference for evaluative interpretations in the physiotherapist practice in Brazilian children and adolescents.